A Cautionary Note on Microcredentialing in Entrepreneurship Education. (July 2021) - Phelan, Steven E.; Glackin, Caroline E.
A recent trend in entrepreneurship education has been the emergence of microcredentials. This note provides some cautionary observations on the current state of microcredentials in entrepreneurship, organized around the themes of credibility, legitimacy, and relevance. It then provides some recommendations for the future development of the field, including creating evaluation mechanisms, establishing international standards in entrepreneurship, undertaking more research to establish credibility, forming alliances, and safeguarding relevance.